(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article examines the difference between the notions of compatibility and valency and distinguishes the types of combinations in the linguistic system. The aim of the article is to investigate the functions and types of combinations as a linguistic category. The article uses deductive, inductive methods and content analysis methods. The criterion of lexical combination in the linguistic system is analyzed. The potential of the combination of Kazakh words has also been considered. The analysis of the linguistic material has led us to the conclusion that lexical word combinations with an indicative component have an appositive potential. The study of the types of word combinations led to the hypothesis that the valency can be not only structural, stylistic, functional, but also semantic. The valency of words, although extremely important, is not dominant in determining their combinatorics. More important here seems to be their position of compatibility in meaning. The valence properties of the Kazakh language are described; the distinctive features of the manifestation of valence properties are revealed. The results of the analysis of valence properties of Kazakh vocabulary can also be used in the study of the valence theory of general linguistics. When studying the valence properties of a language, the analysis of its lexical semantics and the determination of its belonging to semantic groups characterized by a field structure is at the core.